1995
DOI: 10.1029/94wr02978
|View full text |Cite
|
Sign up to set email alerts
|

Sensible Heat Flux From Arid Regions: A Simple Flux‐Variance Method

Abstract: Similarity models in the inner region of the unstable atmospheric boundary layer (ABL) are generally based on four dimensional parameters: buoyancy, friction velocity, surface heat flux, and the height above the land surface. In the free convection limit the friction velocity can be neglected, thus reducing the measurement needs in practical applications. Some field measurements of the second moment of temperature have indicated that free convection scaling of this statistic may be extended into more dynamic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 16 publications
5
55
0
Order By: Relevance
“…The fetch surrounding the instrumented site is uniform for several kilometers. The surface is crusty sand with a mean surface roughness length z o of 0.13 mm; however, the variation around this estimate is large [see Katul, 1994;Albertson et al, 1995].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fetch surrounding the instrumented site is uniform for several kilometers. The surface is crusty sand with a mean surface roughness length z o of 0.13 mm; however, the variation around this estimate is large [see Katul, 1994;Albertson et al, 1995].…”
Section: Methodsmentioning
confidence: 99%
“…The short sampling period was necessary to ensure steady state in the mean meteorological conditions. The mean meteorological parameters such as net radiation, soil heat flux, surface temperature, mean wind speed, and wind direction were also measured during the experiment [see Katul, 1994;Katul et al, 1995a, b;Albertson et al, 1995].…”
Section: Methodsmentioning
confidence: 99%
“…where C 3 ≈ 0.99 (corrected for κ = 0.4) originally determined elsewhere (Wyngaard et al 1971) and verified over a semi-arid area in the region called 'La Crau' in southern France , over a uniform and flat and dry lakebed (Albertson et al 1995), and for several canopies (Wesson et al 2001). Although the φ s (−ζ ) function was experimentally shown to be the same for T , q, and C over a uniform wheat field (Ohtaki 1985), De Bruin et al (1999) studied the correlation coefficient between T and q over a dry vineyard in Spain and concluded that if non-local effects are of the same order as local effects, T and q will be dissimilar.…”
Section: Theorymentioning
confidence: 99%
“…The function φ s (−ζ ) must satisfy two limits (De Bruin 1982;De Bruin et al 1993Albertson et al 1995;Wesson et al 2001):…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation